Search for single top quarks in the tau plus jets channel using 4.8 fb(-1) of p(p)over-bar collision data - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (Elsevier B.V., 2010)
We present the first direct search for single top quark production using reconstructed tau leptons in the final state. The search is based on 4.8 fb(-1) of integrated luminosity collected in p (p) over bar collisions at root s= 1.96 TeV with the D0 detector at the Fermilab Tevatron Collider. We select events with a final state including an isolated tau lepton. missing transverse energy, two or three jets, one or two of them being identified as b quark jet. We use a multivariate technique to discriminate signal from background. The number of events observed in data in this final state is consistent with the signal plus background expectation. We set in the tau + jets channel an upper limit on the single top quark cross section of 7.3 pb at the 95% C.L. This measurement allows a gain of 4% in expected sensitivity for the observation of single top production when combining it with electron + jets and muon + jets channels already published by the do Collaboration with 2.3 fb(-1) of data. We measure a combined cross section of 3.84(-0.83)(+0.89) pb, which is the most precise measurement to date. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Single top; Top quarks; Tau leptons